PENGARUH PRODUK DAN HARGA TERHADAP MINAT BELI CIMORY DI KOTA PADANG - Nurhidayah Nurhidayah; Rose Rahmidani; Rita Syofyan (Jurnal Ecogen, 2018)
This study aims to examine: (1) The effect of the product on buying interest, (2) The effect of prices on buying interest. This type of research is causative. The population in this study was the people of Padang City who knew about Cimory's products. The sampling technique used was purposive sampling with a total sample of 100 respondents. The type of data used in this study is primary data. The data analysis technique uses descriptive and inductive analysis through multiple regression analysis using the SPSS version 21 program. The hypothesis is tested by F test and t test at α = 0.05. The results of this study indicate that: (1) Product has a significant effect on buying interest, (2) Price does not significantly influence buying interest.Keyword: Buying Interest, Product, Price